2020
DOI: 10.3390/w12102889
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soluble Salt Loss via Spring Water on Irrigation-Induced Landslide Deformation

Abstract: Landslide exposes the previously blocked groundwater discharge. High concentrations of soluble salt form salt sinters that can be observed near discharge passages. Based on existing laboratory investigation results of soil leaching and shearing reported in the literature, the effect of the soluble salt loss via spring water on irrigation-induced landslide deformation was studied under large-scale conditions. During our field investigation of landslides in the Heitai terrace of the Yellow River’s upper reaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Distant from the platform's edge, the sinkholes are observed to be evolving into cracks (Figure 11d). Moreover, spring activity persists at the foot of the slope, and our previous research confirmed that the loss of soluble material via the spring is positively correlated with slope deformation (Figure 11f) [35].…”
Section: Potential For Future Landslides On the Heitai Terracesupporting
confidence: 66%
See 2 more Smart Citations
“…Distant from the platform's edge, the sinkholes are observed to be evolving into cracks (Figure 11d). Moreover, spring activity persists at the foot of the slope, and our previous research confirmed that the loss of soluble material via the spring is positively correlated with slope deformation (Figure 11f) [35].…”
Section: Potential For Future Landslides On the Heitai Terracesupporting
confidence: 66%
“…It is worth noting that local small-scale failure occurred near the phreatic line of some landslides, with a high probability of extension into the surrounding area; multi-stage cracks had developed in the sidewalls and crowns of the failure areas, and springs continued to discharge outwards (Figure 3a). Previous studies have confirmed that the soil strength in the spring discharge path is markedly reduced owing to changes in soil properties, and soil deformation is related to the total amount of soluble material lost from the soil interior via spring water [35,37]. In addition, both land use and spring discharge have significant impacts on groundwater [21,59,60], causing an increase in hydraulic gradient and positive pore water pressure owing to the differential rise in groundwater caused by the crop planting structure, which may also contribute to the failure at this site.…”
Section: Type B 1 Loess Landslides-groundwater-relatedmentioning
confidence: 87%
See 1 more Smart Citation
“…The two most common multitemporal technologies are permanent scatterer interferometric synthetic aperture radar (PS-InSAR) [24,25], which is dominated by permanent scatterers, and small baseline subset interferometric synthetic aperture radar (SBAS-InSAR) [26,27], which is dominated by distributed scatterers. The application of these technologies has achieved outstanding results in the study of land subsidence and landslide movement [28][29][30][31][32][33][34]. Remote sensing has also become a conventional method in the monitoring of land surface water [35].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Xue et al [15] documented the influence of soaking time and salt concentration on the behavior of some samples taken from a soil subjected to water irrigation. The problem of the soluble salt loss and its effect on irrigation-induced landslides was also studied by Zhang et al [16].…”
mentioning
confidence: 99%